A biodegradable water-activated battery: using an activated carbon-based anode and a CNT-based air-cathode. Issue 1 (1st March 2022) - Trang Nguyen, Dang; Nguyen, Hoang-Uyen-Dung; Taguchi, Kozo
Abstract: Activated carbon has been popularly utilizing for countless applications such as purification of water, heavy metal removal, and natural gas and biogas storage. In this study, a novel phenomenon of activated carbon powder (ACP) has been utilized to realize a disposable water-activated battery. The battery is environmentally friendly because it is based on an ACP-loaded anode and a multiwalled carbon nanotube-coated air-cathode. The air-cathode was integrated on the backside of a paper-based proton exchange membrane. The battery case was made of cardboard for low cost and biodegradability. The proton exchange membrane was attached to the battery case. The anode was separately fabricated and could be simply set in the battery case for power generation. Because the air-cathode was used, the battery case could be reused for many cycles. The anode could also be reused for some cycles. Although the output power capacity of the battery is low in the range of mW kg −1 of ACP, it is made of low-cost and abundant materials, and therefore being able to be scaled up. The battery is a biodegradable on-demand micropower generation.